Growth-front hopping via stress-induced nucleation illustrated for the crystallization of Ba1-xSrxZn2Si2O7 from a glass in the BaO-SrO-ZnO-SiO2 system. Issue 16 (November 2018) - Thieme, Katrin; Zscheckel, Tilman; Thieme, Christian; Kracker, Michael; Rüssel, Christian; Höche, Thomas
Abstract: The effect of P2 O5 and Ce2 O3 on the crystallization behavior of a BaO-SrO-ZnO-SiO2 glass was investigated using thermal analyses, X-ray diffraction, scanning electron microscopy including electron backscatter diffraction as well as laser scanning microscopy. Heat treatments lead to the precipitation of Ba1-x Srx Zn2 Si2 O7, Zn2 SiO4, and CeO2 at the surface. While Zn2 SiO4 crystals form 1 µm deep immersions in the surface, CeO2 crystals originate from near-surface areas. The star-shaped CeO2 crystals show mostly three different orientations, among which the <001>- or <111>-orientation perpendicular to the surface are clearly preferred. In the bulk, many (Ba, Sr)5 (PO4 )3 Cl crystals are observed acting as nucleation sites for Ba1-x Srx Zn2 Si2 O7 . This nucleation process is clearly facilitated by the occurring stresses. Moreover, an epitaxial growth of Ba1-x Srx Zn2 Si2 O7 on (Ba, Sr)5 (PO4 )3 Cl is indicated. If the surface-crystallized layer consisting of Ba1-x Srx Zn2 Si2 O7 crystals approaches the (Ba, Sr)5 (PO4 )3 Cl crystals in the bulk, nucleation is induced and the thus provoked growth in the same growth direction as the (Ba, Sr)5 (PO4 )3 Cl crystal leads to a shift of the growth front towards the sample volume and hence growth-front hopping occurs.